(3GdeRGL dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd Mfjf (B: (3Led eG ai GdebGdI GdChdi ef cJGH LGdjfhS SHY GdChdi Gf CUfGa GdeRGL JSYI GdKGfjI Cfg jfHZi Cf jbGd Cf GaVdgG gh GdeYJOd ajeG Hjf GdMGQ hGdHGQO s
(3BNQgG (B:s
(3hef GdHjf Cf GdedeSI GdJi jeJMf HgG eG jeJMf , ajfHZi Cf Jchf eYQGI ef cd MQGQI hHQOI eSJaGOI ceG bdfG bHd GdCOhjI CfaSgG JeJ GdebGdI GdKGdKI ef cJGH LGdjfhS ai GdeRGL JQLeI Mfjf Hf ESMGb hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSIs
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B231 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi edi (B(521/6) s
Keywords: (3GdWHs